Role of Age Hardening Heat Treatment on the Hardness Values of 93.95 Al-5 Zn-1.05 Sn/5 Al2o3- Sio2 Particulate Composite - Aondona P. Ihom (Aceh International Journal of Science and Technology, 2014)
Abstract - The effect of age hardening heat treatment on the hardness values of 93.95Al-5Zn-1.05Sn/5Al2O3-SiO2 particulate composite has been studied. The data used for the work was generated at the National Metallurgical Development Centre, Jos Foundry shop, where the composite was developed. The composite was developed using the stir cast method. The result of the work has shown that the composite has a response to age hardening heat treatment with the optimum hardness value occurring at 2 hours of age hardening. A model was developed for the relationship between age hardening time and hardness of the composite. It was tested, and the product moment of correlation and the coefficient of correlation values attested to the degree of correlation existing between the two variables.